"Only Russia Can Save the World": Reactive Orthodoxies, Political Technology, and Religious Worldbuilding - Riccardi-Swartz, Sarah (Temenos, 2025)
Drawing on previous research dedicated to the examination of far right media worlds that link Christian conservatives in the United States and Russia, this talk offers a broad overview of how technology and ideology transform American social ecologies. Contending that digital media are crucial to the social recalibrations of Russian Orthodoxy in the global context, this talk invites us to see better the philosophical connections across local religious beliefs and global politics in our mediated contemporary moment.